2016
DOI: 10.3389/fpls.2016.01554
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Molecular, Phenotypic, and Geographical Diversity to Develop Compact Composite Core Collection in the Oilseed Crop, Safflower (Carthamus tinctorius L.) through Maximization Strategy

Abstract: Safflower (Carthamus tinctorius L.) is a dryland oilseed crop yielding high quality edible oil. Previous studies have described significant phenotypic variability in the crop and used geographical distribution and phenotypic trait values to develop core collections. However, the molecular diversity component was lacking in the earlier collections thereby limiting their utility in breeding programs. The present study evaluated the phenotypic variability for 12 agronomically important traits during two growing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 47 publications
3
61
0
1
Order By: Relevance
“…Another advantage offered by core collections is that these collections often include unrelated individuals (accessions) which decreases the chances of identifying spurious marker-trait associations due to pre-existing population structure. In safflower, evaluation of global germplasm collections identified significant diversity for most of the desirable traits (oil content, fatty acid composition, resistance to biotic and abiotic stresses, and spines) (Ashri, 1975 ; Dwivedi et al, 2005 ; Kumar et al, 2016 ). To facilitate genetic dissection of complex traits, small, operational core collections have been developed in safflower (Johnson et al, 1993 ; Dwivedi et al, 2005 ; Kumar et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another advantage offered by core collections is that these collections often include unrelated individuals (accessions) which decreases the chances of identifying spurious marker-trait associations due to pre-existing population structure. In safflower, evaluation of global germplasm collections identified significant diversity for most of the desirable traits (oil content, fatty acid composition, resistance to biotic and abiotic stresses, and spines) (Ashri, 1975 ; Dwivedi et al, 2005 ; Kumar et al, 2016 ). To facilitate genetic dissection of complex traits, small, operational core collections have been developed in safflower (Johnson et al, 1993 ; Dwivedi et al, 2005 ; Kumar et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In safflower, evaluation of global germplasm collections identified significant diversity for most of the desirable traits (oil content, fatty acid composition, resistance to biotic and abiotic stresses, and spines) (Ashri, 1975 ; Dwivedi et al, 2005 ; Kumar et al, 2016 ). To facilitate genetic dissection of complex traits, small, operational core collections have been developed in safflower (Johnson et al, 1993 ; Dwivedi et al, 2005 ; Kumar et al, 2016 ). These core collections can be effectively used for association mapping provided they demonstrate presence of high genetic variance (for better mapping resolution) and possess weak population structure and low kinship association among individuals (to avoid spurious associations between molecular markers and functional loci) during association analysis (Pritchard et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification, selection, and preservation the genetic of diversity within forest trees species is therefore of particular interest due to the long life spans of these organisms, which require adaption to different environments and climate. These characteristics can be successfully used to inform conservation, efforts, including targeted breeding programs seeking to improve genetic diversity within a provenance [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example Kumar et al () assessed 531 safflower accessions collected from 43 countries and reported high genetic variability in the collection of safflower germplasm with a global distribution. In another study they described development of core collections in safflower using molecular marker data with phenotypic values and geographical distribution (Kumar et al, ). Nevertheless, safflower exhibits somewhat reduced nucleotide diversity as compared to its progenitor, consistent with the occurrence of a population genetic bottleneck during domestication (Chapman & Burke, ).…”
Section: Introductionmentioning
confidence: 99%